Analysis of residual stresses in bioinert inorganic plasma sprayed ceramic coatings - Mrdak, Mihailo R. (Vojnotehnički glasnik / Military Technical Courier, 2018)
One of the factors for a successful application of ceramic coatings on biomedical implants is the compatibility of the physical and mechanical properties of coatings with the metal substrates of implants. Temperature and temperature gradient in the coating during powder deposition play an important role in the final quality of the coating. The coefficients of thermal expansion and thermal conductivity of the coating and the substrate are different, which affects the growth of residual stresses in coatings. To reduce the difference between the physical characteristics of the coating and the substrate to a minimum, the coating surface temperature and the substrate surface temperature must be kept under control during the deposition of powder. It is therefore of particular importance to control residual stresses in ceramic coatings in order to secure service life of coatings and implants. The paper describes a model of plasma heat transfer and predicts the distribution of residual stresses in the deposited coatings; it also describes the radiography techniques for measuring residual stresses in ceramic coatings. The aim of this paper is to describe the effect of powder deposition rates as well as the effect of the changes in the thickness and the thermal conductivity of the ZrO2CaO coating on the level and the sign of residual stresses. The paper also presents the influence of the bonding coating, and the changes in the thickness of bonding and the ceramic ZrO2MgO coating as well as the heat treatment on the level and the sign of residual stresses. It was found that the increase of the total thickness of the coating increases the proportion of residual stresses on the surface and the edges of the coating.